Novel Vitamin D Analogs for Prostate Cancer Therapy. (19th September 2011) - Chen, Tai C.; Kittaka, Atsushi
Abstract : Prostate cells contain specific receptors for 1α, 25-dihydroxyvitamin D [1α, 25(OH)2 D] or calcitriol, the active form of vitamin D. 1α, 25(OH)2 D is known to inhibit the proliferation and invasiveness of prostate cancer cells. These findings support the use of 1α, 25(OH)2 D for prostate cancer therapy. However, 1α, 25(OH)2 D can cause hypercalcemia, analogs of 1α, 25(OH)2 D that are less calcemic but exhibit potent antiproliferative activity would be attractive as therapeutic agents. To accomplish these goals, different strategies, based on metabolism, molecular mechanism of actions, and structural modeling, have been taken to modify the structure of vitamin D molecule with the aims to improve the efficacy and decrease the toxicity of vitamin D to treat different diseases. During the past four decades, over 3, 000 analogs have been synthesized. In this paper, we discuss the development and the biological analysis of a unique class of vitamin D analogs with a substitution at the carbon 2 of 19-nor-1α, 25(OH)2 D3 molecule for potential application to the prevention and treatment of prostate cancer as well as other cancers.